Note—A Dominance Relation in Dynamic Lot Sizing - Williams, Robert F. (Management Science, 1975)
A computationally efficient forward algorithm for the Economic Lot Size Model is developed. It uses a Dominance Relation and the Ordering Cost to limit the solution space. The Dominance Relation developed includes the standard planning horizon theorem. Extensions for price breaks and monotonically nonincreasing production costs are presented.